A comprehensive look at the effect of processing on peanut (Arachis spp.) texture. (1st March 2018) - Lykomitros, Dimitrios; Den Boer, Lara; Hamoen, Remco; Fogliano, Vincenzo; Capuano, Edoardo
Abstract: BACKGROUND: Relationships between process and peanut texture have only been studied in Hypogaea species, and focused on very limited processing conditions. In this study, 94 samples were prepared from a combination of 12 raw materials ( Arachis hypogaea and fastigiata cultivars) and 11 roasting conditions (maceration in water, aqueous glucose and at different pH values followed by frying or baking). Texture was analyzed by a trained sensory panel (spectrum method) and large deformation compression tests (TA/XT2), and the microstructure probed with confocal microscopy and X‐ray tomography. RESULTS: The impact of maceration on 'crispy', 'crunchy' and 'hardness' sensory attributes was significantly larger when adding glucose in this step, whereas the effect of pH was minor. The relationship held for both fried and baked peanuts as well as for both A. hypogaea and fastigiata subspecies. The degree of alveolation was similar in differently processed peanuts, even though sensory attributes were significantly different. CONCLUSIONS: Maceration in different media can yield large textural changes in both peanut species, for both baking and frying. Maceration in glucose solutions can induce much larger textural changes than maceration in water. Quantitative data on alveolation show that microstructure disruption through steam generation cannot explain all the texture differences among processed peanuts. © 2018 Society of Chemical Industry